Pemanfaatan Limbah Tambak Garam Sebagai Koagulan Bittern Untuk Menurunkan Parameter Kekeruhan Pada Limbah Tahu - Pedro Caesariano; Muhammad Abdus Salam Jawwad (Jurnal Serambi Engineering, 2025)
The tofu industry produces wastewater with high turbidity, requiring treatment before being discharged into the environment. This study aims to utilize bittern, a byproduct of salt pond production, as an environmentally friendly alternative coagulant to reduce turbidity in tofu wastewater. Bittern was activated using three types of strong bases Ca(OH)₂, KOH, and NaOH with dosage variations of 40,50,60 mL and concentrations of 4%,6%,8%. The results showed that all activators enhanced the coagulation performance of bittern, with varying effectiveness under each treatment. NaOH provided the best result at a dosage of 50 mL and a concentration of 4%, achieving a turbidity removal efficiency of 95%. KOH reached optimal performance at 50 mL and 6%, with a turbidity removal efficiency of 93%, while Ca(OH)₂ achieved 85% efficiency at 50 mL and 6%. Overall, this study demonstrates that NaOH-activated bittern is an effective alternative coagulant with potential for sustainable application in tofu wastewater treatment.